2021
DOI: 10.51985/olbl1894
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Elastography in Differentiating Benign from Malignant Thyroid Nodules Taking Fine Needle Aspiration Cytology as Gold Standard

Abstract: Objective: To evaluate the diagnostic accuracy of Strain Elastography in differentiating benign from malignant thyroid nodules taking fine needle aspiration cytology as gold standard. Study Design and Setting: It was a cross sectional study conducted at Radiology department of Jinnah Postgraduate Medical Centre, Karachi from May 2019 to June 2020 Methodology: Total 586 patients with complaints of swelling in region of thyroid gland were enrolled in study on which Strain Elastography was performed using linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…Literature review of FNAC findings showed that the study conducted by Agrawal and colleagues found sensitivity 88.8%, specificity 100%, PPV 100% and NPV 95.12% 24 while Jesrani et al, in their elastographic study of benign and malignant thyroid nodules perceived, sensitivity100%, specificity 80.2%, PPV 61.7%, NPV 100% and accuracy 85%. 25 These results are in favour of our study findings for FNAC of thyroid nodules except for the sensitivity which is at a little lower side in our observations. The main limitation is that it was single centered study conducted on small group of population so results could not be generalized in relation to ethnicity.…”
Section: Discussioncontrasting
confidence: 74%
“…Literature review of FNAC findings showed that the study conducted by Agrawal and colleagues found sensitivity 88.8%, specificity 100%, PPV 100% and NPV 95.12% 24 while Jesrani et al, in their elastographic study of benign and malignant thyroid nodules perceived, sensitivity100%, specificity 80.2%, PPV 61.7%, NPV 100% and accuracy 85%. 25 These results are in favour of our study findings for FNAC of thyroid nodules except for the sensitivity which is at a little lower side in our observations. The main limitation is that it was single centered study conducted on small group of population so results could not be generalized in relation to ethnicity.…”
Section: Discussioncontrasting
confidence: 74%